Japanese economic development : - Francks, Penelope (Routledge, 1999)
This newly revised, clearly-presented text looks at Japan's economic history from the nineteenth century through to World War II. Working within a framework based on the theories and approaches of development studies, Francks demonstrates the relevance of Japan's pre-war experience to the problems facing developing countries today, and draws out the historical roots of the institutions and practices on which Japan's post-war economic miracle was based. New features include: